Acute toxicity study of the isomeric mixture of alpha and beta amyrin from Protium heptaphyllum (Aubl.) Marchand - Gislei Frota Aragão; Amaurílio Oliveira Nogueira; Francisco Antônio Félix Xavier Júnior; Janaina Serra Azul Monteiro Evangelista; Paulo Nogueira Bandeira; Camila Fernandes; Maria Elisabete Amaral de Moraes; Ana Maria Sampaio Assreuy (Acta Scientiarum. Biological Sciences, 2023)
The isomeric mixture of alpha and beta amyrin (AMY), present in the resin of Protium heptaphyllum, is popularly used as anti-inflammatory and anti-ulcer. The literature has been demonstrating pharmacological activities of these triterpenes in the central and peripheral nervous systems, and in the gastrointestinal and immunological systems. This study traces a toxicological profile of amyrin, aiming to provide information that may clarify its safety. Nine female Wistar rats (170 to 200 g) were divided into three groups of three animals each (control, amyrin 300 and amyrin 2000 mg kg-1, p.o.), which were evaluated by protocols preconized by the Organization for Economic Co-operation and Development (OECD). Open field Test and Malone Hippocratic Screening Scale were performed. AMY, mostly at 2000 mg kg-1, reduced the number of crossings by 57% vs. saline (22.67 ± 2.40) and the number of rearing by 53% vs. saline (42.67 ± 2.96), but increased the number of grooming by 26% vs. saline (1.66 ± 0.33). AMY (2000 mg kg-1) increased the serum glucose by 77% vs. saline (126.70 ± 4.33 mg dL-1), triglycerides by 50% vs. saline (78.67 ± 2.18 mg dL-1) and uric acid by 65% vs. saline (0.73 ± 0.03 mg dL-1). AMY induced vascular congestion and hemorrhage in the liver, spleen and cerebral cortex. Renal changes (cellular damage, inflammatory infiltrate, tubular protein deposition and glomeruli atrophy) were also seen. In conclusion, AMY decreased rat locomotor activity, caused minor biochemical changes, and altered the morphology of the kidney. The present study may contribute to deepen the knowledge about the safety of AMY, aiming the development of a novel pharmacological product.